Hypoalbuminemia is Associated with Higher 90-Day Mortality and Poor Prognosis in Patients with Esophageal Squamous Cell Carcinoma and Liver Cirrhosis Receiving Radiotherapy-Based Therapy - Hua YY; Kuo MC; Chen YH; Lu HI; Lo CM; Chen Y; Wang YM; Lin YH; Li SH; Huang SY (Cancer Management and Research)
Yu-Yang Hua,1 Ming-Chun Kuo,1 Yen-Hao Chen,1 Hung-I Lu,2 Chien-Ming Lo,2 Yu Chen,2 Yu-Ming Wang,3 Yun-Hsuan Lin,3 Shau-Hsuan Li,1 Shih-Yu Huang1 1Department of Hematology-Oncology, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan; 2Department of Thoracic & Cardiovascular Surgery, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan; 3Department of Radiation Oncology & Proton and Radiation Therapy Center, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, TaiwanCorrespondence: Shau-Hsuan Li; Shih-Yu Huang, Department of Hematology-Oncology, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, No. 123, Dapi Road, Niaosong Dist, Kaohsiung City, 833, Taiwan, Tel +886-7-7317123 ext. 8303, Email lee0624@cgmh.org.tw; a724057@cgmh.org.twBackground: Liver cirrhosis (LC) is common among patients with esophageal squamous cell carcinoma (ESCC) due to shared etiologic factor, alcohol. For non-metastatic ESCC (nmESCC) patients with cirrhosis, surgery is often contraindicated or associated with high morbidity, therefore radiotherapy-based therapy was commonly applied. This study aims to investigate prognosticators for overall survival (OS) in nmESCC and cirrhotic patients receiving radiotherapy-based therapy. Furthermore, we will also evaluate the predictors for the 90-day mortality rate to reduce avoidable treatment-related toxic effects, and prevent medical waste.Methods: Between January 2001 and December 2021, we retrospectively reviewed medical records of 1298 ESCC patients. Total 78 patients with nmESCC and liver cirrhosis identified based on abdominal ultrasonography, computerized tomography, or liver biopsy were enrolled. Clinicopathologic parameters were collected and correlated with OS and 90-day mortality.Results: Univariate analysis revealed that Child-Pugh classification B/C (P< 0.001, versus A), radiotherapy alone (P=0.03, versus chemoradiotherapy), prothrombin time (PT) prolonged≧2 seconds (P=0.024), albumin≦3.5g/dl (P< 0.001), controlled/refractory ascites (P=0.01, versus none of ascites), and total bilirubin≧1.5mg/dl (P=0.004) were significantly associated with inferior OS. In multivariate analyses, albumin≦3.5g/dl (P=0.001, odds ratio (OR): 2.500) and total bilirubin≧1.5mg/dl (P=0.019, OR: 2.012) were independent adverse prognosticators. The 90-day mortality in these 78 patients receiving radiotherapy-based therapy was 10.3% (n=8), including ESCC progression in 4 patients, liver failure in 1 patient, and others in 3. Clinical 8th American Joint Committee on Cancer (AJCC) stage IVA (P=0.02), clinical T classification T3/4 (P=0.049), PT prolonged≧4 seconds (P=0.009), and albumin≦3.5g/dl (P=0.027) were significantly correlated with higher 90-day mortality. Logistic model showed albumin≦3.5g/dl (P=0.015, OR: 16.129) and clinical 8th AJCC stage IVA (P=0.012, OR: 17.544) were independently correlated with higher 90-day mortality.Conclusion: Hypoalbuminemia is associated with higher 90-day mortality and poor prognosis in nmESCC and liver cirrhosis patients receiving radiotherapy-based therapy.Keywords: radiotherapy, esophageal cancer, liver cirrhosis, prognosis, albumin, nutrition